Pengaruh EPS, NPM dan CR terhadap Nilai Perusahaan pada Perusahaan yang Terdaftar di JII70 Periode Tahun 2022-2024 - Ahmad Apriansyah; Hadi Suriono (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The background of this research is based on the importance of financial performance indicators in shaping investor perceptions and influencing firm value in the capital market. This study aims to examine the effect of Earnings Per Share (EPS), Net Profit Margin (NPM), and Current Ratio (CR) on firm value, both partially and simultaneously, in companies listed in the Jakarta Islamic Index 70 (JII70) during the period 2022–2024. This research employs a quantitative method with an associative approach. The population consists of 70 companies listed in JII70, while the sample is selected using purposive sampling, resulting in 11 companies. The data used are secondary data obtained from financial statements published on the official Indonesia Stock Exchange website and company annual reports. Data analysis was conducted using multiple linear regression analysis with the assistance of SPSS version 27 for Windows. The findings show that profitability indicators are more influential than liquidity in determining firm value. Earnings per Share has a significant effect, though its direction is not fully consistent with theoretical expectations, while Net Profit Margin positively and strongly influences firm value. Current Ratio is not significant individually. However, all variables together significantly affect firm value. The model has moderate explanatory power, indicating that external factors such as macroeconomic conditions, market sentiment, and corporate policies also play important roles.